Two new species of nematodes (Nematoda) from highly mineralized rivers of Lake El’ton basin, Russia - Gusakov, Vladimir A.; Gagarin, Vladimir G. (Zootaxa, 2016)
Two new nematode species, Mesodorylaimus rivalis sp. n. and Allodiplogaster media sp. n., from the highly mineralized rivers of the El’ton Lake basin (Russia) are described and illustrated from numerous mature females and males. Mesodorylaimus rivalis sp. n. is similar to M. vulvapapillatus Bagaturia & Eliava, 1966, but differs from it in the longer body, shorter spicules and longer female prerectum. Allodiplogaster media sp. n. resembles A. lupata (Shoshin, 1989) Kanzaki, Ragsdale & Giblin-Davis, 2014 and A. mordax (Shoshin, 1989) Kanzaki, Ragsdale & Giblin-Davis, 2014, but differs from the first species in having a shorter pharynx, shorter outer labial setae, longer spicules and different ratio between anterior and posterior pharynx sections, and from A. mordax in the thinner body, shorter pharynx and longer spicules.